Examining the Prevalence and Risk Factors of School Bullying Perpetration Among Chinese Children and Adolescents - Xue, Jia; Hu, Ran; Chai, Lei; Han, Ziqiang; Sun, Ivan Y. (Frontiers in Psychology, 2022)
School bullying threatens the health of children and adolescents, such as mental health disorders, social deviant behaviors, suicidal behaviors, and coping difficulties. The study addresses (1) prevalence rates of both traditional and cyber school bullying perpetration, and (2) the associations between self-control, parental involvement, experiencing conflicts with parents, experiencing interparental conflict, and delinquent behaviors, and school bullying perpetration among Chinese students and adolescents. This study used a nationally representative school bullying survey (n=3,675) among students from all grades (primary school 4th grade to high school 12th grade) in seven cities in China. Negative binomial regression was used to estimate the effects of these predictive factors on traditional and cyberschool bullying perpetration, respectively. Seven control variables were included, such as gender, boarding school, family socioeconomic status, and parents’ education levels. The sample comprised 52% female students, 18% at boarding school, 70% of the students’ academic performance were average or average above. Approximately 17.5% of the students reported having participated in traditional school bullying against their peers, and 8% perpetrated cyberbullying behaviors. Also, after controlling sociodemographic characteristics, high self-control, parental involvement reduced the likelihood of perpetrating, both traditional and cyberbullying. Experiencing interparental conflict and delinquent behavior were significantly associated with increased traditional and cyberschool bullying perpetration. We found that having a conflict with parents was only significantly associated with cyberbullying perpetration. Anti-bullying intervention programs targeting this population should consider these factors. For example, school administrators may develop school programs involving parents in the efforts and intervention workshops improving students’ levels of self-control.